Increased Duration of Drying–Rewetting Cycles Increases Nitrate Removal in Woodchip Bioreactors. Issue 1 (1st September 2019) - Maxwell, Bryan M.; Birgand, François; Schipper, Louis A.; Christianson, Laura E.; Tian, Shiying; Helmers, Matthew J.; Williams, David J.; Chescheir, George M.; Youssef, Mohamed A.
Abstract : Core Ideas: Nitrate removal in woodchips increased linearly with drying–rewetting duration. Nitrate removal increased up to 172% in the longest drying–rewetting duration. Nitrate removal rates increased proportionally with dissolved organic C leaching. A previously reported experiment showed weekly drying–rewetting (DRW) cycles increase nitrate removal rates in woodchip‐based denitrifying bioreactors. A follow‐up experiment determined the effect of duration of unsaturated conditions on nitrate removal after rewetting. Three different levels of DRW duration were tested in a 105‐d column experiment ( n = 2), with woodchips left unsaturated once a week for either 2 h, 8 h, or 24 h. Increasing duration of unsaturated conditions significantly increased nitrate removal rates. The longest DRW duration of 24 h resulted in the greatest increase in nitrate removal rates, relative to constantly saturated woodchips, with mean rate increases reaching 172% by the end of the experiment. Results suggest nitrate removal in denitrifying bioreactors is carbon limited, with labile carbon made available during aerobic periods of DRW cycles the most likely cause of observed rate increases. Both studies show DRW cycles dramatically increase the nitrate removal efficiency of denitrifying bioreactors.